The Church of England in the First Decade of the 21st Century Findings from the Church Times Surveys - Village, Andrew (Springer International Publishing, 2018)
This book analyzes two large surveys of clergy and lay people in the Church of England taken in 2001 and 2013. The period between the two surveys was one of turbulence and change, and the surveys offer a unique insight into how such change affected grassroots opinion on topics such as marriage, women's ordination, sexual orientation, and the leadership of the Church. Andrew Village analyzes each topic to show how opinion varied by sex, age, education, location, ordination, and church tradition. Shifts that occurred in the period between the two surveys are then examined, and the results paint a detailed picture of how beliefs and attitudes vary across the Church and have evolved over time. This work uncovers some unforeseen but important trends that will shape the trajectory of the Church in the years ahead.